Public management and the results-based budget of the Dirección Regional de Educación Huánuco - Vidal-Chamorro, Ruth I. (2021)
Objective. To determine the relationship between public management and the results-based budget in the Dirección Regional de Educación Huánuco. Methods. The descriptive method was used. The population consisted of 56 workers in charge of planning, executing and monitoring institutional management. The survey and bibliographic compilation were used as data collection techniques; then, in order to analyze the results, they were tabulated, tables and graphs were prepared and interpreted. Results. The results obtained allowed us to demonstrate that public management is significantly related to the budget by results in the Dirección Regional de Educación Huánuco. Conclusion. It is concluded that there is a significant relationship between public management and the budget for results in the Dirección Regional de Educación Huánuco, showing a p-value = 0.000 < 0.05 using the non-parametric chi-square statistical test at 95 % reliability.